Conformational flexibility of GRASPs and their constituent PDZ subdomains reveals structural basis of their promiscuous interactome. (20th January 2020) - Mendes, Luis Felipe S.; Batista, Mariana R. B.; Judge, Peter J.; Watts, Anthony; Redfield, Christina; Costa‐Filho, Antonio J.
Abstract : The Golgi complex is a central component of the secretory pathway, responsible for several critical cellular functions in eukaryotes. The complex is organized by the Golgi matrix that includes the Golgi reassembly and stacking protein (GRASP), which was shown to be involved in cisternae stacking and lateral linkage in metazoan. GRASPs also have critical roles in other processes, with an unusual ability to interact with several different binding partners. The conserved N terminus of the GRASP family includes two PSD‐95, DLG, and ZO‐1 (PDZ) domains. Previous crystallographic studies of orthologues suggest that PDZ1 and PDZ2 have similar conformations and secondary structure content. However, PDZ1 alone mediates nearly all interactions between GRASPs and their partners. In this work, NMR, synchrotron radiation CD, and molecular dynamics (MD) were used to examine the structure, flexibility, and stability of the two constituent PDZ domains. GRASP PDZs are structured in an unusual β3 α1 β4 β5 α2 β6 β1 β2 secondary structural arrangement and NMR data indicate that the PDZ1 binding pocket is formed by a stable β2 ‐strand and a more flexible and unstable α2 ‐helix, suggesting an explanation for the higher PDZ1 promiscuity. The conformational free energy profiles of the two PDZ domains were calculated using MD simulations. The data suggest that, after binding, the protein partner significantly reduces the conformational space that GRASPs can access by stabilizing one particular conformation, in a partner‐dependent fashion. The structural flexibility of PDZ1, modulated by PDZ2, and the coupled, coordinated movement between the two PDZs enable GRASPs to interact with multiple partners, allowing them to function as promiscuous, multitasking proteins. Abstract : GRASPs are Golgi proteins associated with the cisternae organization and unconventional protein secretion. Despite the importance in many cell functionalities, the origins of their high promiscuity in protein–protein interactions remain elusive. In this work, we show that the structural flexibility of PDZ1, modulated by PDZ2, and the coupled, coordinated movement between the two PDZs enable GRASPs to interact with multiple different partners, allowing them to function as promiscuous, multitasking proteins.